Optimalisasi Pendapatan Asli Daerah Provinsi Jawa Barat Sebagai Upaya Mewujudkan Kemandirian Fiskal - Rizky Zakaria; Dede Dede (JURNAL PAJAK INDONESIA, 2022)
The existence of the Covid-19 pandemic has implications for the economic conditions of West Java Province. This includes the revenue and financing of the West Java Provincial Government (West Java Province) which has a deficit of IDR 5.04 trillion in 2020. Therefore, it is necessary to optimize Regional Original Income (PAD) as an effort to realize regional fiscal independence. This study in addition to describing the urgency of optimizing PAD, also efforts that can be made by the Government in maximizing its PAD revenue. The research methodology used in this research is qualitative. The results of this study indicate the urgency of optimizing PAD, because the economic potential in West Java is high; PAD contribution which tends to decrease in regional income; Pandemic conditions that have not yet ended will have an impact on the community's economy; and the actions of the West Java Provincial Government that have not been optimal to increase PAD. Based on this urgency, efforts to optimize PAD that can be carried out include strengthening the commitment of regional heads in optimizing PAD, mapping the potential of all types of taxes, strengthening tax collection and optimization strategies, providing tax incentives, and providing adequate tax infrastructure and human resources. Thus, PAD optimization can be carried out even in the Covid-19 pandemic situation. Adanya pandemi covid-19 berimplikasi pada kondisi ekonomi Provinsi Jawa Barat. Hal ini termasuk pada pendapatan-pembiayaan Pemerintah Provinsi Jawa Barat yang defisit Rp5,04 triliun pada 2020. Oleh karena itu, perlu dilakukan optimalisasi Pendapatan Asli Daerah (PAD) sebagai upaya mewujudkan kemandirian fiskal daerah. Penelitian ini selain menguraikan urgensi dilakukannya optimalisasi PAD, juga upaya yang dapat dilakukan oleh Pemerintah dalam memaksimalkan penerimaan PAD-nya. Hasil penelitian ini menunjukan urgensi dilakukan optimalisasi PAD, karena potensi ekonomi di Jawa Barat yang tinggi; kontribusi PAD yang cenderung mengalami penurunan pada pendapatan daerah; kondisi Pandemi yang belum usai menyebabkan dampak pada perekonomian masyarakat; dan tindakan Pemprov Jabar yang belum optimal untuk m eningkatkan PAD. Atas urgensi tersebut, maka upaya optimalisasi PAD yang dapat dilakukan antara lain dengan penguatan komitmen kepala daerah dalam mengoptimalkan PAD, mapping potensi semua jenis pajak, penguatan strategi pemungutan dan optimalisasi pajak, pemberian insentif pajak, dan penyediaan infrastruktur dan SDM pajak yang memadai.